2013
DOI: 10.2308/accr-50417
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Deferred Tax Assets and Liabilities and Future Tax Payments

Abstract: This study empirically examines whether deferred taxes provide incremental information about future tax payments and explores whether the relationship is affected by whether and when the deferred tax accounts reverse. The analysis provides evidence that while deferred taxes do provide incremental information about future tax payments, the magnitude of the information is small. Further, consistent with theoretical predictions (Guenther and Sansing 2000, 2004; Dotan 2003) the analysis demonstrates there is an as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 21 publications
3
33
0
Order By: Relevance
“…The previous research emphasized tax planning, the minimization of tax liabilities using deferred taxes (Taylor and Richardson, 2012;Laux, 2013), and the impact of such deferment on companies' stock prices (Chaney and Jeter, 1994;Wong et al, 2011). This research contributes to the previous research by exploring to what extent and for what reasons companies avoid full recording of deferred taxes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous research emphasized tax planning, the minimization of tax liabilities using deferred taxes (Taylor and Richardson, 2012;Laux, 2013), and the impact of such deferment on companies' stock prices (Chaney and Jeter, 1994;Wong et al, 2011). This research contributes to the previous research by exploring to what extent and for what reasons companies avoid full recording of deferred taxes.…”
Section: Discussionmentioning
confidence: 99%
“…The study also revealed that a large part of deferred tax items tend to reverse. Laux (2013) finds that investors seem to value only the information content of specific items of deferred tax; he empirically examines whether deferred taxes provide incremental information about future tax payments and explores whether the relationship is affected by whether and when the deferred tax accounts reverse. His analysis provides evidence that while deferred taxes do provide incremental information about future tax payments, the magnitude of the information is small.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an asymmetry of information provided by these two different categories: the gaap first (associated with future tax-related cash flows) and the tax first category (without offsetting the tax effects of reversing temporary differences) (Laux, 2013). Opportunistic book and tax reporting undertaken by managers also yields variations in book-tax differences (Tang, 2015;Hanlon & Heizman, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, in the case of two-book accounting, while the gaap first category is associated with future taxrelated cash flows that are realised upon reversal of deferred tax assets or liabilities, the tax first category is treated in a different way. New originating temporary differences do not offset the tax effects of reversing temporary differences (Guenther & Sansing, 2004;Laux, 2013). The gaap_first variable includes the recognition of transactions by the company based on accounting standards and the principles of prudence and matching.…”
Section: Book-tax Conformity Measuresmentioning
confidence: 99%